BIOMASSA EM Maytenus ilicifolia MART. EX REISS E INDUÇÃO DE FLUORESCÊNCIA DA CLOROFILA a - Dal Comune, Mariane (2016)
Biodiversity conservation is a priority issue in recent decades. The intense extraction of non-timber species has resulted in a loss of biological diversity.The expansion of the medicinal plant market based almost solely on the extraction, has contributed to the decline of the species, so it is necessary to seek solutions and physiological information for sustainable management.The Maytenus ilicifolia species is popularly known as espinheira-santa and is native to the south of the country, widely used in pharmacology field being somewhat related to management aspects. Therefore, this study aimed to analyze the fluorescence induction of chlorophyll a and evaluate biomass production, comparing it to the non-destructive technique of random sampling branches for more information on the species and thus provide an ecological management plan.